Job Satisfaction during the COVID-19 Movement Control Order : A State Wide Study of Utility Companies in Sarawak, Malaysia - Donald, Stephen; Shahren, Ahmad Zaidi Adruce; Victoria, Jonathan (The International Islamic University Malaysia, 2025)
Malaysia ordered a series of lockdowns (known as Movement Control Order) on 18 March 2020 to break the chain of COVID-19 infection within the community. The lockdown imposed brought drastic changes in working practices and thus forced workers to work from home. This paper investigates the changes in job satisfaction before and during the MCO. Utility services were chosen because they are essential services outlined by the Malaysian National Security Council during the COVID-19 pandemic. This study was a state-wide study (in Sarawak, Malaysia), gathering 10,320 employee data over two years (2019-2020). Based on the one-samplet-test, the level of job satisfaction during the COVID-19 pandemic has significantly increased. Future research should investigate possible factors that could explain job satisfaction during the pandemic. Organizations and policymakers should take note of these findings and be vigilant of inconveniences of remote working to preserve a good level of job satisfaction